Tindak Tutur Dalam Transaksi Jual Beli Intan di Pasar Martapura Kabupaten Banjar - Johan Arifin; Fitharatun Nisa; Akhmad HB (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Speech Acts in Diamond Sale and Purchase Transactions at Martapura Market in Banjar Regency. Disclosure of intent and purpose in different language events. In the process of buying and selling, speech between traders and buyers often contains different intentions according to the statement acts used when spoken. This study aims to determine the types of speech acts used in the process of buying and selling diamonds at Martapura Market. This study uses a qualitative approach with descriptive methods. The data obtained in this study comes from the spoken language spoken by traders with traders and traders with buyers who are buying and selling transactions. The source of the data in this study is the recording of the process of buying and selling diamonds at Martapura market and written documents in the form of transcripts of speech. Data collection was obtained by using the referring method and followed by competent involvement techniques and note-taking techniques. The results of this study found the types of speech acts used as follows: 1) representative statement acts, 2) directive speech acts, and 3) expressive speech acts. Representative speech acts are used by traders and buyers to confirm, give reasons, explain, insist, advise, swear, complain, give advice, and notify. The directive speech acts used by traders and buyers are to give orders, requests, restrictions and information. Meanwhile, expressive speech acts are used by traders and buyers to express feelings of worry, pleasure, pronunciation, praise, and apology. The most frequent speech acts found in this study are representative speech acts.